Brugada-type Electrocardiographic Pattern Induced by Fever - Ozeke, Ozcan (Indian Pacing and Electrophysiology Group, 2005)
ST-segment elevation in Brugada syndrome is caused by a shift in the ionic current balance and the creation of a voltage gradient between the epicardium and the endocardium. This ionic mechanism have been shown to be temperature dependent. We describe a 33-year-old man who presented with fever with the dynamic electrocardiographic changes similar to the Brugada syndrome. These electrocardiographic anomalies disappeared when the temperature returned to normal.